2012
DOI: 10.1111/cns.12005
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Edged Sword with Therapeutic Potential: An Updated Role of Autophagy in Ischemic Cerebral Injury

Abstract: SUMMARYCerebral ischemia is a severe outcome that could cause cognitive and motor dysfunction, neurodegenerative diseases and even acute death. Although the existence of autophagy in cerebral ischemia is undisputable, the consensus has not yet been reached regarding the exact functions and influence of autophagy in cerebral ischemia. Whether the activation of autophagy is beneficial or harmful in cerebral ischemia injury largely depends on the balance between the burden of intracellular substrate targeted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 148 publications
(168 reference statements)
4
115
0
Order By: Relevance
“…Autophagy may play a pro‐death or a pro‐survival role of cells 4. A large amount of research have shown that autophagy is a double‐edged sword involved in health and disease 5. Whether autophagy protects or aggravates the renal damage in cisplatin‐induced AKI is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy may play a pro‐death or a pro‐survival role of cells 4. A large amount of research have shown that autophagy is a double‐edged sword involved in health and disease 5. Whether autophagy protects or aggravates the renal damage in cisplatin‐induced AKI is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in other situations, autophagy can be deleterious and contribute to cell death either by triggering apoptosis or necrosis or as an independent cell death mechanism ("autophagic cell death" or type II programmed cell death). 2,3 In neurons the question of whether enhanced autophagy promotes cell death or cell survival is a subject of considerable debate [3][4][5][6][7][8] especially in excitotoxic conditions such as cerebral ischemia. Some studies have suggested a protective role of neuronal autophagy in cerebral hypoxia/ ischemia, 9,10 whereas others have demonstrated a death-mediating role.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a well-known player in cellular homeostasis. Superfluous or damaged proteins and organelles are packed into autophagosomes, which drain into lysosomes for degradation (58,59,70,71). The role of autophagy in cell death, particularly in ischemic cell death, is controversial and under intense study.…”
Section: March 2017mentioning
confidence: 99%
“…The effects of autophagy are likely context dependent. Numerous studies have demonstrated that autophagy is activated following ischemic insult (59,(62)(63)(64)(71)(72)(73). Whether autophagy is a driver of cell death in ischemia is still not clarified.…”
Section: March 2017mentioning
confidence: 99%
See 1 more Smart Citation